Approaches to disruptions and interactions in archaeology : proceedings of the Graduate Archaeology at Oxford Annual Conferences in 2017-2019 - Coombe, Penny,; Fung, Ying Tung, (Access archaeology., 2022)
Here is a collection of papers presented at the Graduate Archaeology at Oxford Conferences 2017-2019. The papers draw out different aspects of the key themes of interaction, mobility, entanglement and disruption amongst various communities and demonstrated through material culture, relating to a range of time periods.